Sistema automático de detecção do sono utilizando células de carga - Santos, Lucas Moraes dos (My University, 2019)
The quality of a person's sleep is directly associated with their health. In view of this, sleep monitoring is an excellent resource for the diagnosis and follow-up of various diseases. Polysomnography, the gold standard for sleep monitoring, is widely used in clinics specializing in sleep medicine. However, because it is an intrusive and expensive method, its continuous and long-term use becomes impracticable. Currently, there are several non-intrusive sleep monitoring techniques under study and development. They seek to remove the need for user intervention on the device. One such technique makes use of load cells positioned under the bed supports as an alternative and non-intrusive method for monitoring sleep. Information about the respiratory rhythm, heart rhythm and movements of the person can be extracted from the acquired signs, which can help in the process of detecting sleep. In view of the above, the present work presents the development of a sleep detection system based on machine learning, able to determine if an individual is in the waking state or sleep, from measurements from load cells coupled to the brackets of the bed. The system was evaluated based on the results obtained for 39 patients, resulting in a sensitivity (awake class) of 50.1% and specificity (sleeping class) of 53.1%. After applying a medium filter on the signal coming from the classification, there was an increase of 2.8% in the sensitivity that remained in 51.5%, while in the specificity was obtained 54.8%, which represents an increase of 3.2 % (sic).
A qualidade do sono de uma pessoa está diretamente associada à sua saúde. Em vista disso, o monitoramento do sono é um excelente recurso para o diagnóstico e acompanhamento de diversas doenças. A polissonografia, padrão-ouro para monitoramento do sono, é amplamente utilizado em clínicas especializadas em medicina do sono. Porém, por ser um método intrusivo e caro, sua utilização contínua e a longo prazo torna-se inviável. Atualmente, existem diversas técnicas de monitoramento do sono, não-intrusivas, em estudo e desenvolvimento. Elas buscam remover a necessidade de intervenção do usuário ao dispositivo. Uma dessas técnicas faz o uso de células de carga posicionadas sob os suportes da cama, como um método alternativo e não- intrusivo para monitoramento do sono. A partir dos sinais adquiridos, podem ser extraídas informações sobre o ritmo respiratório, ritmo cardíaco e os movimentos da pessoa, informações estas que podem auxiliar no processo de detecção do sono. Diante do exposto, o presente trabalho apresenta o desenvolvimento de um sistema de detecção do sono baseado em aprendizado de máquina, capaz de determinar se um indivíduo está no estado de vigília ou sono, a partir de medições advindas de células de carga acopladas aos suportes do leito. O sistema foi avaliado com base nos resultados obtidos para 39 pacientes, resultando em uma sensitividade (classe acordado) de 50,1% e especificidade (classe dormindo) de 53,1%. Após aplicação de um filtro mediana sobre o sinal advindo da classificação, houve um aumento de 2,8% na sensitividade que ficou em 51,5%, enquanto na especificidade obteve-se 54,8%, que representa um aumento de 3,2% (sic).
Keywords: Distúrbios do sono; Sono - Aspectos fisiológicos; Sono - Qualidade; Bioinformática; Engenharia biomédica